Long-Term Colorectal-Cancer Mortality after Adenoma Removal - Løberg, Magnus; Kalager, Mette; Holme, Øyvind; Hoff, Geir; Adami, Hans-Olov; Bretthauer, Michael (The New England journal of medicine, 2014)
This analysis of Norwegian registry data suggests that colonoscopic surveillance during the 8 years after removal of low-risk adenomas is not required for a reduction in colorectal-cancer mortality. Screening programs for colorectal cancer are currently implemented in many Western populations 1 , 2 because randomized trials have documented an association between screening and a sustained reduction in colorectal-cancer mortality. 3 The benefit is most likely due to early detection of cancer, endoscopic removal of adenomas, and surveillance of patients who are considered to be at high risk for the development of new neoplastic lesions. 4 , 5 However, precise quantification of the risk of death from cancer after adenoma removal has been hampered by the scarceness of large, population-based studies with long follow-up periods. Previous studies were performed in populations undergoing intensive surveillance, . . .